2006
DOI: 10.1590/s1516-44462006005000016
|View full text |Cite
|
Sign up to set email alerts
|

Increased dyslipidemia in schizophrenic outpatients using new generation antipsychotics

Abstract: Increased dyslipidemia in schizophrenic outpatients using new generation antipsychotics Dislipidemia aumentada em pacientes esquizofrênicos ambulatoriais em uso de antipsicóticos de nova geração A b s t r a c t Objective: First and second generation antipsychotics are associated with metabolic disturbances. A cross-sectional study was designed to follow outpatients at the Schizophrenia and Dementia Program at a major teaching hospital in Porto Alegre, Brazil (Hospital de Clínicas de Porto Alegre) in order to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…However, one previous study, which assessed some metabolic disturbances associated with MS in schizophrenic outpatients in use of antipsychotics found a high percentage of overweight patients, and increased prevalence of dyslipidemia. 26 Considering that the prevalence rates of DM and obesity in Brazil 27,28 are lower than those in United States, 19,27 we can estimate that the prevalence of MS in our country is inferior to the prevalence of MS (23.7%) found in that country. Thus, the prevalence of MS found in this study (29.4%) is probably higher than that of the general population.…”
Section: Discussionmentioning
confidence: 65%
“…However, one previous study, which assessed some metabolic disturbances associated with MS in schizophrenic outpatients in use of antipsychotics found a high percentage of overweight patients, and increased prevalence of dyslipidemia. 26 Considering that the prevalence rates of DM and obesity in Brazil 27,28 are lower than those in United States, 19,27 we can estimate that the prevalence of MS in our country is inferior to the prevalence of MS (23.7%) found in that country. Thus, the prevalence of MS found in this study (29.4%) is probably higher than that of the general population.…”
Section: Discussionmentioning
confidence: 65%
“…A cross-sectional study of 62 patients with schizophrenia found that increased BMI was associated with dyslipidemia [Kato et al 2005]. Furthermore, Leitão-Azevedo and colleagues showed a significant decrease in HDL cholesterol levels in patients treated with clozapine compared with those treated with first-generation antipsychotics [Leitão-Azevedo et al 2006]. Likewise, for the other metabolic parameters (LDL cholesterol and triglycerides), the study failed to show significant difference between the treatments.…”
Section: Discussionmentioning
confidence: 99%
“…9 The excessive cardiovascular mortality associated with SZ and BD is attributed in part to an increased risk of the modifiable atherosclerotic risk factors: obesity, smoking, diabetes, hypertension and dyslipidaemia. [10][11][12] Inflammation is a mechanism that plays a part not only in atherosclerosis but also in different neuropsychiatric disorders, where it is involved in complex and reciprocal interactions with neurotrophins and oxidative stress. Considering these interactions, a Systemic Toxicity Index for mood episodes has recently been proposed to study neurotrophins, oxidative stress markers and inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%